Brazing Ti-47Al-2Cr-2Nb to Inconel 718 with different filler alloys: microstructural characterization of the interfaces - Guedes, A. (2010)
Vacuum brazing of γ-TiAl alloy (Ti-47Al-2Cr-2Nb, at.%) to Inconel 718 (53Ni-19Fe-19Cr-5Nb-3Mo-1Ti wt.%) using Incusil-ABA (Ag-27.25Cu-12.5In-l.25Ti, wt.%), Nicusil-3 (Ag-28.lCu-0.75Ni, wt.%) and Tini 67 (Ti-33Ni, wt.%) as filler alloys was investigated. The lowest temperatures at which joining was successfully accomplished were 730, 810 and 1200°C for brazing with Incusil-ABA, Nicusil-3 and Tini 67, respectively. The interfaces were examined by scanning electron microscopy (SEM) and chemically analysed by energy dispersive X-ray spectroscopy (EDS). Series of microhardness tests were performed across the brazed joints to assess the interfacial hardness profiles. All filler alloys induced the formation of multilayered interfaces. For joining with either Incusil-ABA or Nicusil-3 most of the interface was softer than both base materials. AlCu 2 Ti was formed at the γ-TiAl alloy side, while near the superalloy (Cu) and Cr-Fe-Ni rich phases were detected. The centre of the interface consisted of a mixture of (Ag), (Cu) and Al(Cu,Ni) 2 Ti. For joining with Tini 67 the interface was harder than both base materials. Reaction layers formed in vicinity of the γ-TiAl alloy were composed of α 2 -Ti 3 Al and TiNiAl, while near the superalloy, TiNi 2 Al and several phases rich in Cr, Fe and Ni were observed. The experiments performed in this investigation showed that brazing with Incusil-ABA allows lowering the brazing temperature of at least 50°C in comparison with Ag-Cu eutectic filler, while brazing with Tini 67 produces harder interfaces and may enhance the temperature capability of the joints in comparison with filler alloys that contain Ag. However, joining using Tini 67 as brazing filler has to be performed at substantially higher temperatures.